Technological Revolutions and Political Economy - Prodanov, Hristo (Research Papers, 2017)
This study focuses on the connection between different technological revolutions, the expansions and cycles of capitalism, the changes in political and economic relations those revolutions bring. The main idea is that the progress of technologies inevitably brings a big change in mainstream politico-economical paradigms that must answer to the needs of every stage of capitalistic cycle. Systematicly, in historical and comparative perspective, and without falling into technological determinism, this study discusses the changes in the economic thought as a result of four different technological revolutions. In this way we have the opportunity to understand and see into the processes that drive the capitalism and impose the dominant paradigms that must answer to the new emerging needs of the economy. Today, with the entrance in the Fourth industrial revolution, we are at the shore of a new and historical changes and crisis, which are shifting the sources of wealth, bringing a big search of new politico-economical paradigms that should explain the new realities and overcome the crisis processes.